Pengaruh Kualitas Chatbot, Kecepatan Respons, dan Kemudahan Informasi terhadap Kepuasan Pelanggan E-Commerce - Alvi Lutfiah Seftianih; Muhammad Surya William Gunawan; Yoaclina Benihingan; Anfaal Ramadhan; Rifkhan (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to examine the effects of chatbot quality, response speed, and information accessibility on customer satisfaction in Indonesian e-commerce. A quantitative causal research design was employed using primary data collected through an online questionnaire distributed to 120 respondents, of which 105 valid responses were obtained (87.5% response rate) through purposive sampling. Data were analyzed using multiple linear regression with the aid of SPSS. The results show that chatbot quality (t = 2.587; sig. = 0.011), response speed (t = 3.750; sig. = 0.000), and information accessibility (t = 2.919; sig. = 0.004) each have a positive and significant partial effect on customer satisfaction. Simultaneously, the three variables significantly affect customer satisfaction (F = 15.342; sig. = 0.000), with response speed emerging as the most dominant predictor. These findings suggest that e-commerce platforms should prioritize chatbot responsiveness alongside service quality and information clarity to enhance customer satisfaction in the digital marketplace.